A Case of Infective Endocarditis Caused by Rapidly Growing Non-tuberculous Mycobacterium after Cardiac Catheterization - Huda, SM Nurul; Kabir, Mohammad Faisal Ibn; Khaled, Md Fakhrul Islam; Anwar, AFM Azim; Amin, Md Rasul (University Heart Journal, 2023)
Endocarditis caused by non-tuberculous mycobacterium is rare and often missed without appropriate blood cultures. It does not respond to standard antitubercular treatment and is also resistant to many other antibiotics. The course of the disease may be indolent and often results in a fatal outcome. Here we report a case of Nontuberculous mycobacterial endocarditis of the native aortic valve in an immunocompetent patient following coronary angiography. The case highlights an unfortunate intervention – related nosocomial infection and the difficulties in chemotherapeutic options for this organism, particularly in the presence of marrow suppression and acute interstitial nephritis. University Heart Journal 2023; 19(1): 31-34